Du traumatisme à l’effacement : la spirale vertigineuse dans Theories of Forgetting de Lance Olsen (2014) - Anthony Remy (Sillages Critiques)
In Theories of Forgetting the protagonists’ drive to put down in writing their own personal and existential thoughts reflects the psychological and psychosomatic troubles from which all three of them suffer, albeit at different levels of intensity. Through the observation of these writing processes Lance Olsen reveals a contemporary metafictional text in crisis as well. By examining concepts such as the conscious and the unconscious, or the importance of memory – both individual and collective – in the construction of one’s own identity, the author underlines the fact that everything is actually doomed to disappear. Paradoxically, this form of erasure becomes an authorial productive gesture in Theories of Forgetting, which is embodied in the topos of the spiral.